The Experience of Bugis Makassar Mothers in Managing Febrile Seizures in Children - Mikawati; I Kade Wijaya (Community Medicine and Education Journal, 2023)
Febrile convulsions are seizures that occur due to an increase in body temperature. Data from the Makassar City Health Office in 2012 reported the incidence of fever of unknown causes as many as 54,782 cases. The study aimed to know the experience of Bugis mothers in handling febrile seizures in children in the working area of the Tamamaung Health Center, Panakkukang Sub-District, Makassar. Qualitative research design with phenomenological study, through semi-structured interviews with in-depth interview method. The number of participants was 6 people obtained by purposive sampling. Data were collected in the form of interview recordings and field notes using the thematic analysis method. There are four points of results, Makassar Bugis mothers understand the description of febrile seizures, Makassar Bugis mothers are able to handle febrile seizure children, Psychological experience of Makassar Bugis mothers in handling febrile seizures, Makassar Bugis mothers' ability to prevent febrile seizures in children. Housewives play an important role in child care at home. Health workers need to increase the knowledge of Makassar Bugis mothers about how to handle febrile seizures at home.